Allying cobalt nanoclusters with carbon nanofibers for selectively electrocatalytic hydrogenation of unsaturated aldehyde with water as hydrogen source - Xinyu Yang; Sheng-Hua Zhou; Xiaofang Li; Xin-Tao Wu; Qi-Long Zhu (Materials Today Catalysis)
The electrocatalytic hydrogenation of α, β-unsaturated aldehydes has attracted significant attention, yet the design of electrocatalysts with selective adsorption over CC or CO bond remaining a challenging task. In this study, the Co nanoclusters anchored onto the nitrogen-doped porous carbon nanofibers were elaborately fabricated for efficient electrocatalytic hydrogenation. A kinetically driven mono-micelle-oriented self-assembly method was applied to synthesize the polymer nanofibers as the accommodation for Co2 +. The stepwise pyrolysis of Co2+/polymer nanofibers with dicyandiamide yielded the evenly distributed Co nanoclusters with an average size of ∼4 nm over the nitrogen-doped porous carbon nanofibers. Benefited from the high activity of the Co nanoclusters and their rapid electron communication with the nitrogen-doped porous carbon nanofibers, this electrocatalyst demonstrated excellent performance in the selectively electrocatalytic hydrogenation of cinnamaldehyde to hydrocinnamaldehyde, achieving a high selectivity of 90.9 % and a conversion of 68.2 % at 12 mA cm−2. The further in-situ spectroscopy analysis and density functional theory calculations revealed the more preferred adsorption of CC bond and easier water dissociation to give the active H atoms over the Co nanoclusters, which shed light on the hydrogenation mechanism over this electrocatalyst. Our study can provide a new insight in catalyst design for electrocatalytic hydrogenation reaction.